COMPETITIVE ADVANTAGE OF STEEL MANUFACTURING FIRM IN CENTRAL SULAWESI, INDONESIA: DSI STEEL INDONESIA - Qing Song; Jacob Donald Tan (FEB Universitas Sam Ratulangi Manado, 2023)
Dexin Steel Indonesia (DSI) is a China-Indonesia joint venture steel company with its headquartered is located at Jakarta and its manufacturing factory is located at Indonesia Morowali Industrial Park, Morowali Regency, Central Sulawesi. Steel market in Indonesia is as fierce as ever, and DSI needs to be stand out among other competitors to thrive in the fierce market. In this qualitative study, the researchers inquired into the issues to explore DSI’s competitive advantage, by employing a single instrumental case study with interviews, observations, and field notes. There are 10 informants who were approached for this study consisting of 5 internal stakeholders and 5 external stakeholders. The findings evinced a mini-model theory that guides DSI in Indonesia to enhance its competitive advantages to be able to survive in the marketplace. The mini-model theory consists of Experienced and Skillful Leadership, Language Barrier, Supportive Parent Company, Commitment to Alliance Agreement, Cultural Awareness, Cost Management, Learning Agility, Advanced Technology and lastly Equipment and Customer Engagement. Finally, the researchers also suggest other possible avenues for further research.